PERAN KEMITRAAN PT SANTY ABADI MANDIRI BERDASARKAN INDIKATOR KEBERHASILAN KEMITRAAN (STUDI PADA PT SANTY ABADI MANDIRI DAN PETANI TALAS TANJUNG BINTANG, LAMPUNG) - Nosa, Mersi Wedia; Agung, Maulana (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
The partnership program between PT Santy Abadi Mandiri and beneng taro farmers in the Tanjung Bintang area was carried out due to limited resources owned by both parties. Each related party has roles and responsibilities that must be fulfilled in order to achieve common goals. The aim of this research is to analyze the role of PT Santy Abadi Mandiri in meeting the need for chopped talas beneng leaves and find out what obstacles occur in implementing partnerships to meet needs. This type of research uses a qualitative approach with primary and secondary data sources. Data collection methods through observation, interviews and documentation. The research results show that, 1). The partnership that PT Santy Abadi Mandiri has established with partner farmers has an important role in running a business in the field of beneng taro farming seen from the indicators of partnership success, namely, Input, Process, Output, Outcome. 2). Obstacles faced by companies in establishing partnerships include the supply of wet taro leaves purchased from partner groups rotting due to unpredictable weather, while the obstacles faced by partner groups in cultivating are the weather being too hot and the cultivated beneng taro plants not growing well. due to the minimal availability of water sources on agricultural land. Research shows that the partnership is carried out using a core plasma partnership pattern. Judging from the partnership indicators, PT Santy Abadi Mandiri as the core company has provided guidance to partner farmer groups, purchased the partner group's harvest, provided production facilities, guaranteed marketing of the harvest and fixed prices. Meanwhile, the partner farmer group as the core has been cultivating beneng taro from start to harvest, selling the harvest to companies and cultivating taro well so that the need for beneng taro chopped leaves can be met through partnerships established between the company and farmers. Keywords: Role of Partnership, Indicator of Partnership Success, Obstacles, Partnership Patterns